Návrh poměrů mísení dvou těžených kameniv frakce 0/4 mm pro výrobu transportbetonu - Jastrzembská, Alena (Vysoké učení technické v Brně. Fakulta stavební, 2026)
Diplomová práce se zabývá návrhem poměrů mísení dvou druhů drobných těžených kameniv pro výrobu transportbetonu. V teoretické části práce jsou shrnuty požadavky z českých technických norem na jednotlivé složky betonu, zejména požadavky na drobné kamenivo. V praktické části pak byly navrženy receptury pro tři třídy betonu, bylo provedeno ověření vlastností betonů v čerstvém i ztvrdlém stavu a na základě výsledků pak byl stanoven optimální poměr mísení drobného kameniva z lokality Smiřice a Lípa.

This diploma thesis describes with mixing ratio of two kinds of small quarried aggregate for the production of ready mix concrete. The theoretical part summarizes the requirements of Czech technical standards to individual components of concrete, particularly the requirements for fine aggregates. In the practical part were designed the recipes for three classes of concrete and was done checking the properties of concrete in fresh and hardened state. Based on the results were determined the optimal mixing ratio of fine aggregate from location Smiřice and Lípa.
Design of mixing ratio of two quarried aggregates fraction 0/4 mm for readymix concrete
Keywords: Transportbeton; cement; drobné kamenivo; frakce; Smiřice; Lípa; Čeperka; třída pevnosti betonu; Readymix concrete; cement; fine stone; fraction; Smiřice; Lípa; Čeperka; strength class of concrete